Enhancing Community Understanding of Forest and Land Fire Prevention and Management through Socialization Activities in Musi Banyuasin Regency - Jun Harbi; Andri Abbas; Irkhamiawan Ma'ruf; Rahmat Kurniawan; Elva Dwi Harmilia; Martin Nardi; Heripan (Universitas Muhammadiyah Palembang, 2025)
Forest and land fires are recurring environmental problems in Musi Banyuasin Regency, particularly in areas dominated by forest landscapes and peatlands. This community engagement activity aimed to enhance community understanding and awareness of forest and land fire prevention and management through an educational and participatory socialization approach. The activity was conducted in Muara Merang Village, Bayung Lencir Subdistrict, and Pangkalan Bulian Village, Batanghari Leko Subdistrict, involving 45 participants representing village governments, Fire Care Community groups, farmer and forest farmer groups, youth organizations, and women’s groups. The implementation stages included an initial assessment and site selection, coordination with village stakeholders, pre-test administration, delivery of conceptual and technical materials, participatory discussions, and evaluation through post-test. The results indicate that the community’s initial understanding of forest and land fires was relatively adequate, with an average pre-test score of 6.2, although the understanding remained partial. After the socialization activity, participants’ understanding increased significantly, as reflected by an average post-test score of 9.25. Participatory discussions further revealed community needs for institutional strengthening, more intensive training, adequate equipment support, and sustainable land management alternatives without burning practices. These findings highlight the importance of community-based approaches as an initial step in strengthening local preparedness and sustainable forest and land fire prevention at the village level.